Versatile non-Hermitian piezoelectric metamaterial beam with tunable asymmetric reflections - Wu, Zheng; Yi, Jianlin; Xia, Rongyu; Chen, Jianlin; Li, Zheng (Frontiers in Physics, 2022)
Non-Hermitian systems have been widely utilized to achieve specific functions for manipulating abnormal wave motion, such as asymmetric mode switching, unidirectional zero reflection (UZR), and unidirectional perfect absorption (UPA). In this paper, a novel non-Hermitian piezoelectric metamaterial beam is proposed to realize the tunable UZR of flexural waves. The unit cell of this non-Hermitian metamaterial beam consists of a host beam and two pairs of piezoelectric patches shunting different resistor–inductor circuits. Based on the flexural wave theory, the transfer matrix method is introduced to analyze the influence of electrical boundary conditions on the UZR and further clarify the relationship between the UZR and the exceptional point. The exceptional point depends only on the dissipative circuit, and it has no need for the balanced gain and loss like parity–time symmetric metamaterial. Furthermore, the UZR for the desired frequency is realized by applying a genetic algorithm, and its effectivity is experimentally validated. In addition, the non-Hermitian metamaterial beam is designed to realize the UPA of flexural waves. Results indicate that the proposed metamaterial beam is versatile and can achieve tunable manipulations of asymmetric wave propagations and has widely promising applications in many fields, such as non-destructive testing, enhanced sensing, wave isolation and vibration attenuation.